Food Safety Study: Borax, Formaldehyde, Methanil Yellow, and Total Plate Count in Yellow Tofu Producers in Kediri - Sabrina Wahyu Faradiba; Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Yellow tofu is a traditional food product that is highly perishable due to its high moisture Yellow tofu has a high moisture content (86%) and moderate protein content (8–12%), resulting in a short shelf life of only 1–2 days at room temperature. These characteristics may encourage the misuse of hazardous additives such as formaldehyde, borax, and metanil yellow to preserve texture, color, and shelf life. This study aimed to detect borax, formaldehyde, and metanil yellow, analyze Total Plate Count (TPC), and examine the relationship between sanitation hygiene practices and TPC in yellow tofu produced in Kediri, a major center of tahu takwa production. Samples from 13 producers were analyzed using qualitative and quantitative methods. The results showed that borax and metanil yellow were not detected in any samples. Although 76.92% of samples tested positive for formaldehyde qualitatively, quantitative analysis indicated levels below the detection limit. TPC analysis revealed that 61.5% of samples exceeded the SNI limit of 1×10? CFU/g, with an average of 1.15×10? CFU/g. A significant relationship was found between sanitation hygiene and microbial count (p = 0.002), indicating that proper hygiene practices are essential for maintaining yellow tofu safety. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger SDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production